Molecular Origins of the Zeta Potential - Předota, Milan; Machesky, Michael L; Wesolowski, David J (Langmuir, 2016)
The zeta potential (ZP) is an oft-reported measure of the macroscopic charge state of solid surfaces and colloidal particles in contact with solvents. However, the origin of this readily measurable parameter has remained divorced from the molecular-level processes governing the underlying electrokinetic phenomena, which limits its usefulness. Here, we connect the macroscopic measure to the microscopic realm through nonequilibrium molecular dynamics simulations of electroosmotic flow between parallel slabs of the hydroxylated (110) rutile (TiO2) surface. These simulations provided streaming mobilities, which were converted to ZP via the commonly used Helmholtz-Smoluchowski equation. A range of rutile surface charge densities (0.1 to -0.4 C/m2), corresponding to pH values between about 2.8 and 9.4, in RbCl, NaCl, and SrCl2 aqueous solutions, were modeled and compared to experimental ZPs for TiO2 particle suspensions. Simulated ZPs qualitatively agree with experiment and show that "anomalous" ZP values and inequalities between the point of zero charge derived from electrokinetic versus pH titration measurements both arise from differing co- and counterion sorption affinities. We show that at the molecular level the ZP arises from the delicate interplay of spatially varying dynamics, structure, and electrostatics in a narrow interfacial region within about 15 Å of the surface, even in dilute salt solutions. This contrasts fundamentally with continuum descriptions of such interfaces, which predict the ZP response region to be inversely related to ionic strength. In reality the properties of this interfacial region are dominated by relatively immobile and structured water. Consequently, viscosity values are substantially greater than in the bulk, and electrostatic potential profiles are oscillatory in nature.